“Let the business cycle!” A spatial multilevel analysis of cycling to work - Thomas Vanoutrive; Laurent Van Malderen; Bart Jourquin; Isabelle Thomas; Ann Verhetsel; Frank Witlox (Belgeo, 2009)
The daily commute is still the main source of traffic congestion. Despite transport research emphasis on commuters, the work end of home to work travel receives less attention. However, employers influence the commute behaviour of employees in different ways. The Belgian database Home-to-Work-Traffic (HTWT) contains information on accessibility, work regimes and mobility management initiatives of 7460 worksites of large employers in Belgium. In a spatial multilevel regression model both contextual and worksite factors are incorporated to investigate the share of cycling employees. While controlling for different economic, physical and other factors, the provision of bicycles by the employer seems to be successful, while the effect of bicycle facilities is less clear, partly due to the fact that bicycle facilities are more popular in less cycle-friendly areas.